Adoption of Digital Technology and Marketing in Enhancing SMEs Business Performance - A Musfirah; Aslam Jumain (Penerbit Goodwood, 2026)
Purpose: This study examines the effects of technology adoption and digital marketing on the performance of Small and Medium Enterprises (SMEs), with Human Resource (HR) readiness tested as a mediating variable. Methodology/approach: A quantitative, cross-sectional survey was conducted with 300 SMEs in Kecamatan Manggala, Kota Makassar. Data were analyzed using partial least Squares–Structural Equation Modeling (PLS-SEM), including reliability, validity, and structural diagnostics. Results: All seven hypotheses were supported. Technology adoption and digital marketing exert positive and significant effects on HR readiness and SME performance. HR readiness has a direct positive impact on performance and mediates the relationships between technology adoption, digital marketing, and business outcomes. The indirect effect through HR readiness is stronger for digital marketing than for technology adoption, underscoring the central role of human capacity in digital transformation. Conclusions: Strengthening HR readiness is essential for converting digital adoption into higher SME performance. Programs that combine technology deployment with training and change management support are likely to yield greater and more sustainable performance gains for urban SMEs in developing countries. Limitations: This study is limited to SMEs in one urban district, uses cross-sectional self-reported data, and does not account for wider contextual factors, such as policy, infrastructure, or market conditions. Contributions: This study shows that HR readiness is a key mechanism through which technology adoption and digital marketing enhance SME performance, based on evidence from urban SMEs in a developing-country context, and highlights the need to align digital initiatives with human resource development to achieve sustainable performance gains.